Constructing therapeutic narratives - ʿOmer, Ḥayim 1949-; Allôn, Naḥî (Aronson, 1997)
We must pitch portrayal against portrayal, plot against plot, theme against theme, and meaning against meaning. It will not do, however, simply to oppose a new story to the old one. To succeed, the new story must be close to the client's experience so that it is his or her story; on the other hand, it must be different enough so as to allow for new meanings and options to be perceived. The client is redescribed as the person he could become, once free from the problem's yoke
Keywords: Constructivism (Psychology); Narration (Rhetoric); Narrative therapy; Personal construct therapy; Psychoanalytic Interpretation; Psychoanalytic Therapy -- methods; Reconstruction (Psychoanalysis); Self-perception; Psychotherapie; Persönlichkeitskonstrukt; Erzählen